KIMIA DARAH KUDA INDONESIA YANG DIPELIHARA DI DAERAH ISTIMEWA YOGYAKARTA DAN JAWA TENGAH - , REGINA MICHELA WIBAWA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Horse is one of the livestock which has declined population from year to year. One of the factors that lead the decline of population is diseases. Therefore it is necessary to identify normal standard of blood biochemistry to describe normal horse organs. The objectives of this research is to get a normal standard of horse blood biochemistry that include Serum Glutamic Pyruvic Transaminase (SGPT), Serum Glutamic Oxaloacetic Transaminase (SGOT), Blood Urea Nitrogen (BUN) and Creatinine of Indonesian horse which were maintained in Special District of Yogyakarta and Central Java. The result of the research are expected to become one of the references value for veterinary clinic and useful to diagnose horse disease. Being used 28 Indonesian horse maintained in Special District of Yogyakarta and Central Java. Blood samples were evaluated SGPT, SGOT, BUN and Creatinine level. Horse that become the sample is horse that clinically healthy and doesnât show any disablement, pathological or parasite. Blood sample taking process use 10 ml disposable syringe without anticoagulant stored 5 ml through the jugular vein. Then disposable syringe be tilted diagonally to obtain serum. The horse serum were analyzed by using automatic blood analyzer model RT-1940C (Synchron clinical system CX5CE, Beckam USA). Blood chemistry data analyzed with One Way ANOVA and then Post Hoc Tukey HSD. The result showed that range value Serum Glutamic Piruvic Transaminase (SGPT) by 4,1-20,5 IU /L, Serum Glutamic Oxaloacetic Transaminase (SGOT) by 198,9-333,3 IU /L, Blood Urea Nitrogen (BUN) by 10,8-20,2 mg/dL, and Creatinine by 1,2-2 mg/dL. Result of the research shows that the value of Indonesia horse SGPT, SGOT, BUN and Creatinine in between of normal blood horse chemistry in foreign country and literature.